2007
DOI: 10.1109/lcomm.2007.070761
|View full text |Cite
|
Sign up to set email alerts
|

Network anomaly detection using nonextensive entropy

Abstract: Detection is a crucial step towards efficiently diagnosing network traffic anomalies within an Autonomous System (AS). We propose the adoption of nonextensive entropya one-parameter generalization of Shannon entropy-to detect anomalies in network traffic within an AS. Experimental results show that our approach based on nonextensive entropy outperforms previous ones based on classical entropy while providing enhanced flexibility, which is enabled by the possibility of finetuning the sensitivity of the detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…In general, if the parameter denoted as α has a positive value, it exposes the main mass, if the value is negative -it refers to the tail. Ziviani et al [81] investigated Tsallis entropy in the context of the best value of α parameter in DoS attacks detection. They found that α-value around 0.9 is the best for detecting such attacks.…”
Section: Detection Via Feature Distributionsmentioning
confidence: 99%
“…In general, if the parameter denoted as α has a positive value, it exposes the main mass, if the value is negative -it refers to the tail. Ziviani et al [81] investigated Tsallis entropy in the context of the best value of α parameter in DoS attacks detection. They found that α-value around 0.9 is the best for detecting such attacks.…”
Section: Detection Via Feature Distributionsmentioning
confidence: 99%
“…It has been shown that measuring nonextensive entropy is an effective method to detect anomalies in network traffic within an Autonomous System [37]. Given the success shown here using compression ratios as an alternative measure to entropy, it would indicate that compression-based analysis may also prove similarly effective in other domains where entropy is a distinguishing feature.…”
Section: Compression Ratio Thresholdmentioning
confidence: 85%
“…Although it has been noted before that entropy is not all things to all applications, for example see [3,9,11], this is the first study we are aware of which provides a rigorous quantitative analysis and a systematic investigation. We believe that the insights are very valuable for more general settings and also that the techniques can be extended to analyse more realistic attack scenarios.…”
Section: Our Main Contributions: I)mentioning
confidence: 92%